"Comparative Constitutional Law and Legal Culture: Asia and the Americas": an overview of the CRN01 under the Law and Society Toronto, 2018 Meeting DOI: 10.5935/2448-0517.20180025 - Duarte, Fernanda; Filho, Rafael Mario Iorio; da Silva, Ronaldo Lucas (Juris Poiesis - Qualis A3, 2018)
CRN1 Report - LSA Toronto Metting, 2018